Effectiveness of a Dietary Management Intervention on Modifiable Cardiovascular Risk Factors among Adults with Chronic Heart Disease in Tobruk, Libya: A Three-Month Prospective Study - Lemamsha , Hamdi; Abdelnabi, Kawthar Abdul Fattah; Ali, Rahma Abdul Latif; Abdulati , Roaya Miftah; Soliman, Israa Toafik (Sharwes Scientific Journal, 2026)
Cardiovascular disease remains a leading cause of mortality in Libya, while structured dietary-management programmes for adults with chronic heart disease remain limited, particularly in Tobruk. Existing literature supports the role of dietary modification in cardiovascular prevention; however, evidence regarding culturally adapted interventions in low-resource Libyan clinical settings remains scarce. This study aimed to evaluate the effect of a three-month dietary-management intervention on modifiable cardiovascular risk factors among adults with chronic heart disease in Tobruk. A quasi-experimental prospective pre-post design with a non-equivalent comparison group was adopted. Forty participants aged between 30, and 70 years were recruited from Tobruk Medical Center and Tobruk General Hospital and equally allocated to intervention and comparison groups. The intervention included weekly nutrition education focusing on salt reduction, fruit and vegetable intake, healthy fat choices, cooking practices, and physical activity. Data were collected at baseline and after three months using structured questionnaires and clinical measurements, including blood pressure and body weight. Statistical analysis was conducted using SPSS version 28. Salt-restriction practices were significantly associated with cardiovascular risk-factor improvement (r = 0.61, p < 0.001; t = 8.42, df = 19). Fruit and vegetable intake also showed significant associations (r = 0.58, p < 0.001). Healthy fat and cooking practices demonstrated positive effects (r = 0.55, p < 0.001), while physical activity showed the strongest association with improvement (r = 0.63, p < 0.001). The findings suggest that structured, culturally adapted, low-cost dietary counselling may support cardiovascular risk reduction and improve patient self-management in resource-limited Libyan settings.